Judaism of the Second Temple period - Flusser, David, 1917-2000. (Grand Rapids, Mich. : William B. Eerdmans Pub. Co. ; Jerusalem, Israel : Hebrew University Magnes Press, 2007)
David Flusser was a very prolific scholar of the Dead Sea Scrolls, and his contributions to Scrolls research, apocalypticism, and apocalyptic literature are inestimable. With this English translation of many of his essays, Flusser's insights are now available to a wider audience than ever before. Here Flusser examines the influence of apocalypticism on various Jewish sects. He states that the teachings of Jesus, while reflecting first and foremost the views of the sages, were also influenced by Jewish apocalypticism. Examining the Essenes, their effect on Hebrew language, the split of sects, and much more, Flusser's collected essays offer an important source of study for any Dead Sea Scrolls scholar. - Publisher.
v. 1. Qumran and apocalypticism -- v. 2. The Jewish sages and their literature.
V. 1. Qumran and apocalyptism.
Includes bibliographical references and indexes.
Keywords: Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D.; Jewish sects -- History; Jews -- History -- 586 B.C.-70 A.D.; Qumran community; Apocalyptic literature -- History and criticism